Nxopaxopo wa vukanakanisi eka ririmi ra xitsonga - Sithole, Hlongolwana Sylvia (My University, 2016)
Refer to document
An analysis of ambiquity in Xitsonga langauge
Thesis (M.A. (African Languages)) -- University of Limpopo, 2016
Keywords: Tsonga language; Ambiguity; Language and languages; Tsonga language; Ambiguity; Grammar, Comparative and general